Role of autophagy and oxidative stress to astrocytes in fenpropathrin-induced Parkinson-like damage. (May 2021) - Wu, Yixuan; Jiao, Zhigang; Wan, Zhiting; Qu, Shaogang
Abstract: Fenpropathrin is an insecticide that is widely used in agriculture. It remains unknown whether fenpropathrin exposure increases the risk of Parkinson's disease. We found that fenpropathrin increased oxidative stress both in vitro and in vivo . Additionally, fenpropathrin increased production of ROS, NOS2, and HO-1, and decreased SOD and GSH in astrocytes. We further found that fenpropathrin-mediated oxidative stress might inhibit autophagic flow, including decreased expression of LC3A/B and enhanced expression of SQSTM1 via down-regulation of CDK-5, an upstream marker of autophagy. In mice, autophagy was slightly different from that found in astrocytes, as reflected in the increased expressions of LC3A/B and SQSTM1. Our findings elucidate the toxicological phenomena and pathogenic mechanisms of fenpropathrin and may provide guidance for improved pesticide control and environmental protection. Highlights: Fenpropathrin induces oxidative stress and decreases antioxidant capacity in primary astrocytes of mice. Fenpropathrin inhibits autophagic flow via oxidative stress-mediated reduction of CDK5 in primary astrocytes of mice. Fenpropathrin-treated mice partially mimic the pathological features of Parkinson's disease. Oxidative stress increases in fenpropathrin-treated mice, and autophagy is ameliorated differentially from that of astrocyte.